Automatização informacional de sistemas hidrossanitários prediais por meio de tecnologia BIM e RA - Dariva, Matheus Alves (2021)
Deficiencies in the design process of plumbing systems can be mainly due to the late involvement of designers in the project design and their discontinued and punctual participation, not including the development of "as built" and post-occupancy assessments. The BIM methodology fits into this scenario as a way to explore new technologies to improve project production and increase productivity at construction sites. Augmented Reality (AR) is another technology that can benefit the entire team in the construction, operation and maintenance of an enterprise, proposing a change that does not only happen in the design stage, but also in the construction stage. However, there is a certain scarcity in researches that focus on the application of BIM and RA for analysis of construction information, especially when it comes to plumbing systems. In this scenario, the proposal of this contribution is the development of a technological artifact that allows exploring and analyzing the solutions and information of building facilities from RA, measuring, to a certain degree, how much this technology can contribute to the analysis process and construction. The intention is to improve access to the information necessary for the execution of certain hydro-sanitary systems, reducing errors in works that cause waste and compromise the efficiency and functionality of these installations. The adoption of qualitative analysis of questionnaires answered by professionals from 3 different works was the method of evaluating the contributions of the artifact. The results showed a positive response from users and indicated that the proposed artifact provides highly comprehensive, mobile and effective access to information on building facilities, with great potential to significantly reduce execution errors in works.